Can azathioprine/6-mercaptopurine treatment be withdrawn in patients with response in ulcerative colitis: What is the most appropriate time for this? - Gökhan KABAÇAM,; Murat TÖRÜNER, (Turkish Journal of Gastroenterology, 2019)
-